Vascular invasion predicts the subgroup of lung adenocarcinomas ≤2.0 cm at risk of poor outcome treated by wedge resection compared to lobectomyCentral MessagePerspective - Lina Ma, MD, MS; Travis B. Sullivan, MS; Kimberly M. Rieger-Christ, PhD; Ilyas Yambayev, MD; Qing Zhao, MD, PhD; Sara E. Higgins, MD; Osman H. Yilmaz, MD; Lila Sultan, MS; Elliot L. Servais, MD; Kei Suzuki, MD; Eric J. Burks, MD (JTCVS Open, 2023)
Background: Recent randomized control trials (JCOG0802 and CALGB140503) have shown sublobar resection to be noninferior to lobectomy for non–small cell lung cancer (NSCLC) ≤2.0 cm. We have previously proposed histologic criteria stratifying lung adenocarcinoma into indolent low malignant potential (LMP) and aggressive angioinvasive adenocarcinomas, resulting in better prognostication than provided by World Health Organization grade. Here we determine whether pathologic classification is reproducible and whether subsets of adenocarcinomas predict worse outcomes when treated by wedge resection compared to lobectomy. Methods: A retrospective cohort of 108 recipients of wedge resection and 187 recipients of lobectomy for stage I/0 lung adenocarcinomas ≤2.0 cm was assembled from 2 institutions. All tumors were classified by a single pathologist, and interobserver reproducibility was assessed in a subset (n = 92) by 5 pathologists. Results: Angioinvasive adenocarcinoma (21%-27% of cases) was associated with worse outcomes when treated with wedge resection compared to lobectomy (5-year recurrence-free survival, 57% vs 85% [P = .007]; 5-year disease-free survival [DSS], 70% vs 90% [P = .043]; 7-year overall survival, 37% vs 58% [P = .143]). Adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA), and LMP exhibited 100% 5-year DSS regardless of the surgical approach. Multivariable analysis showed that angioinvasion, tumor size, margin status, and extent of nodal sampling were significantly associated with recurrence but not with surgical procedure. There was substantial interobserver reproducibility among the pathologists for the diagnosis of angioinvasive adenocarcinoma (κ = 0.71) and the combined indolent AIS/MIA/LMP group (κ = 0.74). Conclusions: The majority (∼75%) of lung adenocarcinomas ≤2 cm are adequately managed with wedge resection; however, angioinvasive adenocarcinomas (∼25%) treated by wedge resection with suboptimal nodal sampling exhibit poor outcomes, with a 40% to 45% rate of recurrence within 5 years and 60% to 65% overall mortality at 7 years.